(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background:Parkinson’s disease (PD) is the second most common degenerative neurologic disorder after Alzheimer’s disease. Pain is one of the major clinical symptoms of Parkinson’s disease, occurring in 50-83% of patients. Pathways mediating pain are complex and include basal ganglia and thalamocortical-basalganglia circuits. Objective:To quantitatively assess pain perception in Parkinson disease patients, by determining pain threshold in patients with and without pain through using electrical stimulation. Methods: A cross sectional observational study recruiting 18 patients with a clinical diagnosis of Parkinson disease and healthy controls from the neurologic unit in Al-Kadhimiya teaching hospital in Baghdad; between May 2010 to Jan 2011. There were 13 men and 5 women with a mean age of (66.5 ± 10.2 years). The control group includes 18 healthy subjects, [12 males/ 8 females] with a mean age of 56.6±6.74 years. Quantitative sensory testing was carried at the neurophysiology laboratory in Al-Kadhimiya hospital; using bipolar stimulating electrodes on the forearm, index finger, mid leg, and big toe. Results:Fourteen Out of 18 patients (77.7%) reported pain, while 4 (22.3%) had no pain. There was a highly significant statistical difference in electrical perception between the affected and unaffected side, and between Parkinson disease patients and the controls. There was no statistically significant difference between males and females [p =0.8248], and between patients with and those without pain [p =0.3279]. And between upper and lower limbs on the affected side [p =0.1412], and body side involvement whether right or left in both the patients and controls. Conclusion:Chronic pain is present in 77.7% of Parkinson disease. Patients with Parkinson disease had lower pain threshold compared to controls. The affected side had lower pain threshold. The left or right body side and gender had no effect on pain threshold. Key worlds:Parkinson disease, Pain